Synthesis, Characterization and in vitro Antimicrobial, Anticancer Activity of Random Copolyester using Orcinol - Sivaramakrishnan, T.; Elango, G. (Asian Journal of Chemistry, 2021)
In present study, a novel random copolyester i.e. poly(3-oxy-5-methylphenyl-4-oxynaphthal-1-yl)isophthalate (PONI) was synthesized through solution polycondensation methodology involving orcinol, 1,4-naphthalene diol and isophthaloyl chloride and its solubility in common solvents along with viscosity measurements were performed. The structure of the repeat units in the polyester chain were ascertained based on the spectral characterization of UV-visible, FTIR, 1H & 13C NMR techniques. Thermal analysis of the copolyester were performed by TGA and DSC studies. The activation energy for thermal decomposition of polyester was estimated by well-known kinetic methods. The surface morphology and crystalline nature of the polymer were explored by employing SEM and WAXD methods. The antimicrobial efficacy of copolyester was assessed through well-diffusion method using a Gram-positive and a Gram-negative bacteria. The in vitro cytotoxicity of the polyester prepared was verified against HeLa cell line using MTT assay.